Assessing validity and reliability of social media as an empowerment tool for a group at risk in Malaysia - Norsiah Abdul Hamid; Mohd Sobhi Ishak; Norhafezah Yusof (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article discusses a study on empowerment of a group at risk via social media in Malaysia which focuses on five important dimensions namely economy, social and cultural, legal, political, and psychology. The group at risk focused in the study refers to women. The study employed a survey that uses a set of online questionnaire distributed to women who are actively using social media, particularly social networking sites. This study involves a sample of 1,307 respondents in an exploratory study, in which a 5-factor 24-item instrument to measure empowerment comprising of the five hypothesised dimensions were being developed. Results confirm factor structures of the empowerment model and suggest a more parsimonious instrument for each; a 5-factor 15-item scale for social media empowerment, as compared to the result of pilot study conducted. Goodness-of-fit indices for the model are presented. The result shows that the five dimensions are significant to the empowerment model of women in Malaysia. The findings can contribute greatly to a better understanding of the empowerment mechanism behind social media issues pertaining to women.